Metabolite Quantification by Fourier Transform Infrared Spectroscopy in Diatoms: Proof of Concept on Phaeodactylum tricornutum - Scarsini, Matteo; Thurotte, Adrien; Veidl, Brigitte; Amiard, Frederic; Niepceron, Frederick; Badawi, Myriam; Lagarde, Fabienne; Schoefs, Benoît; Marchand, Justine (Frontiers in Plant Science, 2021)
Diatoms are feedstock for the production of sustainable biocommodities, including biofuel. The biochemical characterization of newly isolated or genetically modified strains is seminal to identify the strains that display interesting features for both research and industrial applications. Biochemical quantification of organic macromolecules cellular quotas are time-consuming methodologies which often require large amount of biological sample. Vibrational spectroscopy is an essential tool applied in several fields of research. A Fourier transform infrared (FTIR) microscopy based imaging protocol was developed for the simultaneous cellular quota quantification of lipids, carbohydrates, and proteins of the diatom Phaeodactylum tricornutum. The low amount of sample required for the quantification allows the high throughput quantification on small volume cultures. A proof of concept was performed (1) on nitrogen-starved experimental cultures and (2) on three different P. tricornutum wild-type strains. These results are supported by the observation in situ of lipid droplet by confocal and brightfield microscopy. The results show that despite the genetic clones of two ecotypes of P. tricornutum, major differences exist in the regulation of the lipid metabolism.